THE REALITY OF SCIENCE TEACHERS’ USE OF E-LEARNING PLATFORMS AND THE OBSTACLES THEY FACE - Dr. Majida Khalaf Khaleel Al-Sbou (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study aimed to identify the reality of science teachers’ use of electronic educational platforms and the obstacles they face, and the study relied on the descriptive and analytical approach, and the study population consisted of (185) teachers working in public schools in Karak governorate, and the study sample reached (81) teachers And a teacher, they were randomly assigned. The results of the study showed that the reality of science teachers’ use of electronic educational platforms came with a positive level, with an arithmetic average (3.53). The obstacles facing science teachers in using electronic educational platforms came in a high degree with a mean of (3.90). The results also showed that there are no statistically significant differences in the reality of Science teachers use online platforms according to variables: (gender, educational qualification, and job experience). The study recommended the necessity to hold courses and workshops for teachers and students to enhance their use and practice of electronic educational platforms, and to train them on the methods of their use, and the study also recommended the necessity of modifying science curricula to match their application through electronic educational platforms in an interactive manner.